To solve the equation \(-3r - 3 = -12\), we'll go through the steps systematically.
-
Start with the equation:
\(-3r - 3 = -12\) -
Add 3 to both sides:
\(-3r - 3 + 3 = -12 + 3\)
\(-3r = -9\) -
Divide both sides by -3:
\(\frac{-3r}{-3} = \frac{-9}{-3}\)
\(r = 3\)
To summarize, the steps taken were:
- Start with \(-3r - 3 = -12\)
- Add 3 to both sides to get \(-3r = -9\)
- Divide both sides by -3 to find \(r = 3\)
Summary of Missing Terms and Descriptions:
-
Missing Terms:
- First step: "Add 3 to both sides"
- Second step: "Divide both sides by -3"
-
Simplified Result:
- \(r = 3\)
You might include "Combine like terms" in the context only if there were more terms to combine, but in this case, the operations performed do not specifically require combining like terms as no additional terms beyond the operations were present.